One-Visit Behavioral Intervention for Older Primary Care Patients with Mild to Moderate Depressive Symptoms. Issue 8 (August 2016) - Gum, Amber M.; Schonfeld, Lawrence; Tyler, Susan; Fishleder, Sarah; Guerra, Lucy
Abstract : Objectives: We pilot tested a one-visit behavioral intervention with telephone follow-up for older primary care patients with mild to moderate depressive symptoms. Methods: A total of 16 English-speaking primary care patients aged 60 years and older who scored 5 to 14 on the Patient Health Questionnaire-9 (PHQ-9) engaged in the intervention visit. Outcomes were assessed at baseline and 4 weeks: activity goals, readiness to change (University of Rhode Island Change Assessment), PHQ-9, Generalized Anxiety Disorder-7, World Health Organization Disability Assessment Schedule 2.0, and satisfaction. Results: The 14 participants who completed the study met or exceeded 73% of activity goals on average. They also improved on all outcomes ( P < 0.05) with medium (University of Rhode Island Change Assessment, GAD-7) to large effect sizes (PHQ-9, World Health Organization Disability Assessment Schedule 2.0), and they were satisfied. Conclusions: This pilot study provided preliminary evidence that a one-visit behavioral activation intervention is acceptable and feasible and improves outcomes. If findings are confirmed, then this intervention could be integrated into existing collaborative care programs. Abstract : In their open pilot study, the authors evaluated a one-visit behavioral intervention with telephone follow-up for older primary care patients with mild to moderate depressive symptoms. The behavioral activation intervention focused on helping patients to do more valued, enjoyable activities. Participants improved in their activity level, depressive symptoms, anxiety symptoms, and disability, and they were satisfied.